Influence of Temperature, Light and Burial Depth on Germination and Emergence of Phalaris minor Seeds - GURVINDER KAUR; AXAY BHUKER; MS HARISH; VS MOR (Seed Research, 2025)
Weed infestation, particularly by objectionable species like Phalaris minor, poses a significant challenge in seed production due to its morphological similarity to wheat and persistence in agricultural fields. Effective management of such weeds requires a clear understanding of their germination ecology. This study was conducted in the Department of Seed Science and Technology, CCS HAU Hisar to assess the effects of temperature, light/darkness, and burial depth on the germination behaviour of freshly collected Phalaris minor seeds. The findings indicated that alternating temperature and light conditions significantly influenced seed germination and emergence. Seeds showed no dormancy and germinated optimally at an alternating temperature of 15/20°C under a 16-hour light and 8-hour dark cycle. Field emergence was highest at a burial depth of 4 cm, with seeds capable of emerging from depths up to 8 cm. The results underscore the importance of environmental factors in managing P. minor and provide valuable insights for developing targeted weed control strategies.